2019
DOI: 10.1021/acs.est.9b04889
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Full-Scale N2O Emission Characteristics and Testing of Control Concepts in an Activated Sludge Wastewater Treatment Plant with Alternating Aerobic and Anoxic Phases

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…In other words, the joint interaction effects between temperature, NO 3 – –N, NH 4 –N, and influent flow rate are implied to drive the variability in N 2 O dynamics in the studied plant, which is operated as alternating between aerobic and anoxic periods. This is, in fact, in agreement with our previous work, which has revealed the importance of elevated NO 3 – –N concentration at the end of aerobic cycles combined with insufficient carbon source where the following anoxic phase leads to incomplete denitrification of N 2 O concentration in the liquid phase during the anoxic phase. As N 2 O is not completely denitrified during the anoxic phase, it is then stripped in the next aerobic phase, thereby contributing to the N 2 O emissions from the plant.…”
Section: Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other words, the joint interaction effects between temperature, NO 3 – –N, NH 4 –N, and influent flow rate are implied to drive the variability in N 2 O dynamics in the studied plant, which is operated as alternating between aerobic and anoxic periods. This is, in fact, in agreement with our previous work, which has revealed the importance of elevated NO 3 – –N concentration at the end of aerobic cycles combined with insufficient carbon source where the following anoxic phase leads to incomplete denitrification of N 2 O concentration in the liquid phase during the anoxic phase. As N 2 O is not completely denitrified during the anoxic phase, it is then stripped in the next aerobic phase, thereby contributing to the N 2 O emissions from the plant.…”
Section: Results and Discussionsupporting
confidence: 93%
“…Overall, both Sobol and Kucherenko methods successfully complement each other and confirm the importance of the key process parameters that affect the N2O dynamics in the plant. While these findings are known from process engineering knowledge and operational experience 12,21 , the advantage of GSA is that it provides a quantification of the relationship. The latter is important when deciding on potential control strategies for the plant.…”
Section: Understanding N2o Emission Characteristic With Global Sensit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The four tested N 2 ORB from the two different nos Z types have distinct biokinetic traits at different temperatures (Figure 1), indicating that temperature is one of the potential factors governing the abundance and composition of the N 2 ORB communities. Seasonal temperature variations are often observed in WWTPs, where N 2 O emissions are correspondingly changed (Chen et al, 2019). Similarly, the temperature dependence of bioreactor performances is also reported (Watanabe et al, 2017), with lower observed N 2 O consumption activity at a low temperature (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a long‐term monitoring campaign were used to quantify full‐scale N 2 O emission of an WRRF operating an activated sludge system with aerobic and anoxic phases (Chen et al., 2019). A relatively low N 2 O emission was reported during seasons with decreasing water temperature trends.…”
Section: Ghg Emissions From Wrrfsmentioning
confidence: 99%